Semitau; Dari Hutan Menjadi Onderafdeling Pada Masa Penjajahan Belanda - Basuki Wibowo; Agus Dediansyah (Universitas Veteran Bangun Nusantara, 2025)
Semitau in 1936 was a part of Afdeling Sintang. This research aims to find out and explore the history of Semitau, which was originally a forest until finally it became an onder afdeling under the Afdeling Sintang area. The method used in this research is historical which consists of heuristics, criticism, interpretation and historiography. The results of the research explain that Semitau before Abang Umar Juned's arrival was a forest. Semitau became even busier after the Dutch from Majang Island moved offices, barracks (dormitories) and warehouses and placed a Gouvernement representative, namely a Controleur, in Semitau until 1936 making it an under afdeling.